Triple-Tissue Sampling during Endoscopic Retrograde Cholangiopancreatography Increases the Overall Diagnostic Sensitivity for Cholangiocarcinoma (Gut and Liver, 2014)
Background/AimsThere are several methods for obtaining tissue samples to diagnose malignant biliary strictures during endoscopic retrograde cholangiopancreatography (ERCP). However, each method has only limited sensitivity. This study aimed to evaluate the diagnostic accuracy of a combined triple-tissue sampling (TTS) method (on-site bile aspiration cytology, brush cytology, and forceps biopsy).Methods : We retrospectively reviewed 168 patients with suspicious malignant biliary strictures who underwent double-tissue sampling (DTS; n=121) or TTS (n=47) via ERCP at our institution from 2004 to 2011.Results : Among the 168 patients reviewed, 117 patients (69.6%) were eventually diagnosed with malignancies. The diagnostic sensitivity for cancer was significantly higher in the TTS group than the DTS group (85.0% vs 64.9%, respectively; p=0.022). Furthermore, the combination of brush cytology and forceps biopsy was superior to the other method combinations in the DTS group. With respect to cancer type (cholangiocarcinoma vs noncholangiocarcinoma), interestingly, the diagnostic sensitivity was higher for cholangiocarcinoma in the TTS group than the DTS group (100% vs 69.4%, respectively; p<0.001) but not for the non-cholangiocarcinoma patients (57.1% vs 57.1%, respectively).Conclusion : sTTS can provide an improved diagnostic accuracy in suspicious malignant biliary strictures, particularly for cholangiocarcinoma.